A domain of the hepadnavirus capsid protein is specifically required for DNA maturation and virus assembly. - Yu, M (1991)
Mutations introduced into the capsid gene of duck hepatitis B virus (DHBV) were tested for their effects on viral DNA synthesis and assembly of enveloped viruses. Four classes of mutant phenotypes were observed among a series of deletions of covering the 3' end of the capsid open reading frame. Class I mutant capsids were able to support normal single-stranded and relaxed circular viral DNA synthesis; class II mutant capsids supported normal single-stranded DNA synthesis but not relaxed circular DNA synthesis; class III mutant capsids resembled class II capsids, but viral DNA synthesis was inhibited 5- to 10-fold; and class IV capsids were severely restricted in their ability to support viral DNA synthesis. Class I capsids were assembled into enveloped virions, but class II, III, and IV capsids were not. Viral DNA synthesized inside class II capsids was normal with respect to minus-strand DNA initiation, plus-strand DNA initiation, and circularization of the DNA, but plus strands failed to be elongated to mature 3-kb DNA. The results suggest that a function of the capsid protein specifically required for viral DNA maturation is also required for assembly of nucleocapsids into envelopes. Thus, class II mutants appear to be defective in the appearance of the "packaging signal" for virus assembly (J. Summers and W. Mason, Cell 29:403-415, 1982).